Substrate-Dependence of Competitive Nucleotide Pyrophosphatase/Phosphodiesterase1 (NPP1) Inhibitors - Lee, Sang-Yong; Sarkar, Soumya; Bhattarai, Sanjay; Namasivayam, Vigneshwaran; De Jonghe, Steven; Stephan, Holger; Herdewijn, Piet; El-Tayeb, Ali; Müller, Christa E. (Frontiers in Pharmacology, 2017)
Nucleotide pyrophosphatase / phosphodiesterase type 1 (NPP1) is a membrane glycoprotein involved in the hydrolysis of extracellular nucleotides. Its major substrate is ATP which is converted to AMP and diphosphate. NPP1 was proposed as a new therapeutic target in brain cancer and immuno-oncology. Several NPP1 inhibitors have been reported to date, most of which were evaluated versus the artificial substrate p-nitrophenyl 5’-thymidine monophosphate (p-Nph-5’-TMP). Recently, we observed large discrepancies in inhibitory potencies for a class of competitive NPP1 inhibitors when tested versus the artificial substrate p-Nph-5’-TMP as compared to the natural substrate ATP. Therefore, the goal of the present study was to investigate whether inhibitors of human NPP1 generally display substrate-dependent inhibitory potency. Systematic evaluation of nucleotidic as well as non-nucleotidic NPP1 inhibitors revealed significant differences in determined Ki values for competitive, but not for non- and un-competitive inhibitors when tested versus the frequently used artificial substrate p-Nph-5’-TMP as compared to ATP. Allosteric modulation of NPP1 by p-Nph-5’-TMP may explain these discrepancies. Results obtained using the AMP derivative p-nitrophenyl 5’-adenosine monophosphate (p-Nph-5’-AMP) as an alternative artificial substrate correlated much better with those employing the natural substrate ATP.